Cryptococcus neoformans in faeces of feral and homing pigeons (Columba livia) in Lima, Peru - Timmermann F., Ricardo (2020)
The aim of this study was to determine the prevalence of Cryptococcus neoformans in faeces of domestic pigeons (Columba livia) in public places in the city of Lima, Peru, in 2015-2016. Samples of dried faeces were collected from pigeon lofts from captive-bred racing pigeons and from public places for free-living pigeons. The samples were processed and cultured on Sabouraud dextrose agar and incubated at 37 °C up to 10 days. Colonies were identified through macroscopic evaluation, capsule visualization with Indian ink, urease test, sugar assimilation, rapid nitrate reduction, phenol oxidase test and growth on CGB agar. A frequency of 5.16% (16/310) of positive samples for C. neoformans in faeces of both types of pigeons was determined. In the faeces of homing pigeons was 8.89% (16/180), while there were no positive samples in the captive-bred racing pigeons. The stochastic Beta Pert simulation (@Risk 5.5®) a minimum and maximum prevalence for the study of 4.59 and 5.61%, respectively. Cryptococcus neoformans is present in the feces of homing pigeons in the city of Lima, Peru.